2018
DOI: 10.1111/1462-2920.14374
|View full text |Cite
|
Sign up to set email alerts
|

Thermodesulfobium sp. strain 3baa, an acidophilic sulfate reducing bacterium forming biofilms triggered by mineral precipitation

Abstract: Sulfate reducing prokaryotes are promising candidates for the remediation of acidic metal-rich waste waters. However, only few acidophilic species have been described to date. Chemolithoautotrophic strain 3baa was isolated from sediments of an acidic mine pit lake. Based on its 16S-rRNA gene sequence it belongs to the genus Thermodesulfobium. It was identified as an acidophile growing in artificial pore water medium in the range of pH 2.6-6.6. Though the highest sulfate reduction rates were obtained at the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 94 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…However, it is now well established that SRB can exist at a much lower pH, as long as sufficient carbon exists in the system (Koschorreck 2008). SRB have been reported in different low pH-environments, such as peatlands (Pester et al 2010), macroscopic microbial streamers and mats (Rowe et al 2007), freshwater sediments impacted with AMD (Herlihy and Mills 1985), acidic pit lake sediments (Koschorreck et al 2003;Rüffel et al 2018), acidic mine tailings in Canada (Praharaj and Fortin 2004), Chile (Diaby et al 2007), and Siberia (Karnachuk et al 2005), moderately acidic (pH ≈ 4) sediments around flooded mine workings in the USA (Church et al 2007), and Rio Tinto sediments in Spain (Sánchez-Andrea et al 2011, 2013. However, although this is still a matter of some controversy, in all of these reports, sulfate reducers could possibly perform sulfidogenesis in less acidic micro-niches, and therefore did not necessarily need to be tolerant of extreme acidity.…”
Section: Geomicrobiological and Biotechnological Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is now well established that SRB can exist at a much lower pH, as long as sufficient carbon exists in the system (Koschorreck 2008). SRB have been reported in different low pH-environments, such as peatlands (Pester et al 2010), macroscopic microbial streamers and mats (Rowe et al 2007), freshwater sediments impacted with AMD (Herlihy and Mills 1985), acidic pit lake sediments (Koschorreck et al 2003;Rüffel et al 2018), acidic mine tailings in Canada (Praharaj and Fortin 2004), Chile (Diaby et al 2007), and Siberia (Karnachuk et al 2005), moderately acidic (pH ≈ 4) sediments around flooded mine workings in the USA (Church et al 2007), and Rio Tinto sediments in Spain (Sánchez-Andrea et al 2011, 2013. However, although this is still a matter of some controversy, in all of these reports, sulfate reducers could possibly perform sulfidogenesis in less acidic micro-niches, and therefore did not necessarily need to be tolerant of extreme acidity.…”
Section: Geomicrobiological and Biotechnological Implicationsmentioning
confidence: 99%
“…SRB have been shown to be very efficient in bioreactors treating acid mine drainage (Nancucheo et al 2017). These microorganisms have been shown to be effective scavengers of dissolved toxic elements such as aluminum or arsenic, either with isolated strains (Rüffel et al 2018) or using a consortium of different species (Falagán et al 2017b;Le Pape et al 2017). Moreover, SRB can be used to selectively precipitate valuable metals like Cu or Zn from AMD (Nancucheo et al 2012).…”
Section: Geomicrobiological and Biotechnological Implicationsmentioning
confidence: 99%
“…In this context, underground environments have attracted wide attention because of the peculiar metabolic processes and microbial community structures featuring these oligotrophic ecosystems and because of the interesting mutual interactions established between microorganisms and minerals [4, 6, 7]. In particular, the importance of cell-mineral interaction was pointed out by the fact that biomineralization processes positively influence biofilm growth and microbial activity [8]. Several studies have demonstrated the strong influence of mineralogy and fluid composition on subsurface microbial diversity [3, 9]; in turn, the microbial activity has shown to have an impact on the mineral formations and cave speleogenesis [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Td. acidiphilum grows at 37-65°C but has a similar pH range to the mesophilic isolates (3.7-6.5), though a closely related isolate (strain 3baa) has been reported to grow between pH 2.6 and 6.6 (Rüffel et al, 2018).…”
Section: Acidophilic Sulfate-and Sulfur-reducing Prokaryotesmentioning
confidence: 99%